LENSECTOMY IN THE TREATMENT OF PATIENTS WITH PRIMARY ANGLE- CLOSURE GLAUCOMA (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Primary zClosed-angle glaucoma (CAG) is one of the complex forms of primaryglaucoma, which often leads to blindness and low vision.